Design and Control of a Novel Detachable Driving Module for Electrification of Manual Wheelchairs - Lee, Dongyoung; Kim, Soonkyum (Institute of Electrical and Electronics Engineers Inc., 2023)
We developed a detachable electric module that converts a manual wheelchair into an electric wheelchair. The existing electric module requires several parts to be fastened to the wheelchair, which complicates its assembly. In addition, because the overall size of the wheelchair increases after its assembly and the turning radius increases compared to the manual wheelchair, controlling the wheelchair becomes difficult for the user. To compensate for these shortcomings, a new type of electric module composed of two omni-wheel driving units is proposed in this study. Because the two modules can independently move forward or backward and change directions, the same movement as that of the existing manual wheelchair is possible. In addition, a mechanism for easy attachment and detachment is proposed and its versatility is verified by mounting it on various wheelchairs. For the stable operation of the module, field-oriented control was applied, and the wheelchair was controlled for stably moving against external forces and ground disturbances according to the module mounting location. A driving test was conducted according to the mounting location of the developed module, and the proposed driving module and applied algorithm were verified through statistical analysis.